The KELAYAKAN SERAT LIDAH MERTUA (SANSEVIERIA TRIFASCIATA) SEBAGAIBAHAN PEMBUATAN BULU MATA PALSU UNTUK RIAS WAJAH SEHARI-HARI (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstrack. The tongue-in-law thrives in every yard, garden, and roadside. However the existence of an abundant tongue-in-law is underutilized by the society, especially in the field of beauty. Tongue-in-law (Sansevieria) has long and smooth leaf fibers, almost similiar with human hair. Therefore, the tongue-in-law fibers are processed into false eyelashes to support the results of daily makeup. The purpose of this study wre to find out the validity of falseeyelashes that made by tongue-in-law fibers and to determine the advisability of false eyelashes made by tongue-in-law fibers for daily makeup in terms of sensory and preference test. The method of this research used experimental method. The object of the study were 5 models of false eyelashes from tongue-in-law fibers, namely BM1, BM2, BM3, BM4, and BM5. This research took place in September 2019 – March 2020. The results of the study based on the analysis of sensory test data showed that all product were considered very suitable with an average percentage of 86.25%. while the results of the favorite test showed that all products were very fond category with an average percentage of 85%.